A graphene electrode material and its preparation method and application

By using microstructure optimization and surface chemical modification techniques in graphene electrode materials, graphene electrode materials with multi-stage pores are prepared, which solves the problems of insufficient desalination capacity and energy utilization efficiency in the existing CDI technology, and achieves efficient capacitive deionization and heavy metal ion removal.

CN115818795BActive Publication Date: 2025-04-22HEBEI UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211658670.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-22
Publication Date
2025-04-22
Estimated Expiration
2042-12-22

AI Technical Summary

Technical Problem

In the existing CDI technology, there is still room for improvement in the desalination capacity and energy utilization efficiency of graphene electrode materials, and the controllability of in-situ carbon nanotubes is not high.

Method used

Through microstructure optimization and surface chemical modification, graphene electrode materials with multi-stage pores were prepared, and three-dimensional honeycomb structures were prepared by chemical etching and hydrothermal method, and the surface oxygen-containing functional group content was adjusted in combination with plasma treatment technology.

Benefits of technology

It significantly improves the seawater desalination performance of CDI technology and the removal performance of heavy metal ions in salt-containing wastewater, reduces energy consumption, and improves energy utilization efficiency. The adsorption capacity can reach 35.66 mg/g, and the Coulomb efficiency can reach 0.84.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115818795B_ABST
    Figure CN115818795B_ABST
Patent Text Reader

Abstract

The present invention relates to a graphene electrode material and a preparation method and application thereof, wherein the preparation method comprises the following steps: (1) uniformly mixing graphene oxide and a chemical etchant, and obtaining a graphene hydrogel through hydrothermal treatment; the obtained graphene hydrogel is sequentially subjected to soaking, freeze drying and annealing treatment to obtain a graphene foam; (2) grinding the graphene foam obtained in step (1), mixing it with a composite conductive agent and an organic solvent, and then coating and drying it to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment to obtain the graphene electrode material. The present invention prepares a graphene electrode material with multi-level pores through microstructure optimization and surface chemical modification, thereby improving the desalination capacity of the capacitive deionization technology, reducing the energy consumption of the desalination process, and achieving the goal of efficient capacitive deionization and desalination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitive deionization and desalination, and in particular to a graphene electrode material and a preparation method and application thereof. Background Art

[0002] Factors such as rapid population growth, worsening industrial pollution and large agricultural water consumption have led to a serious water shortage crisis. Since the earth is rich in seawater and alkaline water resources, producing fresh water through desalination technology has become an effective way to solve the shortage of water resources. Traditional desalination technologies such as multi-effect evaporation, multi-stage flash evaporation, electrodialysis or reverse osmosis face problems such as high investment costs, large energy consumption and low energy efficiency. Capacitive deionization (CDI) is an electrochemical adsorption desalination technology based on the double-layer principle. It can achieve efficient desalination to obtain fresh water at room temperature, pressure and low voltage operation, and has the advantages of easy operation, environmental friendliness and high energy efficiency.

[0003] The electrode material in CDI is crucial to the performance of CDI. The ideal CDI electrode material should have a high specific surface area, suitable pore structure, high ion mobility, high conductivity and good wettability, and be made of low-cost, scalable and easy-to-process materials. Carbon materials have performed most prominently in the application of CDI, among which graphene has attracted widespread attention for its advantages such as high theoretical specific surface area, good desalination ability, high conductivity and adjustable microstructure.

[0004] J. Li et al. (J. Li, B. Ji, R. Jiang, P. Zhang, N. Chen, G. Zhang and L. Qu, Carbon, 2018, 129, 95-103.) chemically etched graphene oxide (GO) with H2O2 (30wt%) at 100°C for 6h, and then freeze-dried it with a trace amount of ethanol in a certain proportion to obtain a three-dimensional graphene aerogel with a rich pore structure. After calcination at 200°C, its mechanical properties were improved. Finally, it was used in CDI for desalination in the form of a self-supporting electrode. At 2.0V, the adsorption capacity in NaCl solution (572mg / L) was 29.6mg / g.

[0005] K. Weiqing et al. (K. Weiqing, D. Xidong, G. Yongjie, L. Hongtao, H. Jiawen and D. Xiangfeng, Nano Research, 2016, 9, 2458-2466.) added GO (20 mL, 2 mg / mL) and H2O2 (200 μL, 30 wt%) into a polytetrafluoroethylene reactor, and obtained a porous graphene hydrogel (HGH) after hydrothermal treatment at 180 ° C for 6 h in an oven. In order to further reduce graphene, HGH was kept at 100 ° C for 2 h in a sodium ascorbate solution (1 M), and a 3 mm thick HGH slice was pressed on a nickel foam to prepare an electrode for CDI desalination test. At a voltage of 1.2 V, the adsorption capacity of 40 mL NaCl solution (5000 mg / L) at a flow rate of 25 mL / min was 26.8 mg / g.

[0006] The above contents all use graphene oxide to prepare CDI electrode materials, but their corresponding adsorption capacity still needs to be further improved.

[0007] CN102583654A discloses a method for preparing a carbon nanotube / graphene sandwich structure nanocomposite capacitor desalination electrode. In the composite electrode material of the invention, carbon nanotubes are evenly supported between graphene layers to form a sandwich structure, and one end of the carbon nanotube is connected to the peeled graphene. By chemical vapor deposition on the graphene surface, carbon nanotubes are grown in situ to achieve low-cost, large-scale preparation of carbon nanotube / graphene sandwich structure nanocomposite materials; the carbon nanotube / graphene sandwich structure nanocomposite materials are mixed with polytetrafluoroethylene emulsion and evenly applied on graphite paper, and then dried to obtain a carbon nanotube / graphene sandwich structure nanocomposite capacitor desalination electrode. However, the controllability of the in-situ grown carbon nanotubes in the preparation method is not high, and there is still room for improvement in terms of increasing desalination capacity, reducing energy consumption and improving energy utilization efficiency.

[0008] In view of the shortcomings of the existing technology, it is urgent to provide an electrode material with high desalination performance and energy utilization efficiency. Summary of the invention

[0009] The purpose of the present invention is to provide a graphene electrode material and a preparation method and application thereof, and to prepare a graphene electrode material with multi-level pores by adopting microstructure optimization and surface chemical modification methods, thereby improving the seawater desalination performance of CDI technology and the heavy metal ion removal performance of saline wastewater, significantly reducing energy consumption and improving energy utilization efficiency.

[0010] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a graphene electrode material, the preparation method comprising the following steps:

[0012] (1) uniformly mixing graphene oxide and a chemical etchant, and subjecting the mixture to a hydrothermal treatment to obtain a graphene hydrogel; and sequentially subjecting the obtained graphene hydrogel to a soaking, freeze-drying, and annealing treatment to obtain a graphene foam;

[0013] (2) The graphene foam obtained in step (1) is ground and mixed with a composite conductive agent and an organic solvent, and then coated and dried to obtain a graphene electrode precursor; the obtained graphene electrode precursor is treated with plasma to obtain the graphene electrode material.

[0014] The preparation method provided by the present invention makes full use of the microstructure optimization and surface chemical modification of the graphene electrode material. Firstly, a three-dimensional honeycomb graphene porous structure having a large number of micropores and mesopores is prepared by chemical etching and hydrothermal method, thereby increasing the specific surface area of ​​the electrode material, increasing the adsorption sites of ions, promoting the rapid transmission of ions, and thus improving the desalination capacity of the CDI technology; then, the reduction degree of the material is regulated by controlling the annealing temperature of the graphene hydrogel, promoting the rapid transmission of electrons, and obtaining an electrode material with excellent conductive properties, thereby reducing the energy consumption of the desalination process of the CDI technology; the present invention also adopts plasma treatment technology to regulate the content of oxygen-containing functional groups on the surface of the graphene electrode material with multi-level pores, thereby increasing the hydrophilicity of the electrode material, promoting the infiltration of aqueous solution, and accelerating the rapid transmission and adsorption of ions.

[0015] Preferably, the volume ratio of the graphene oxide to the chemical etchant in step (1) is (100-3000):1, for example, it can be 100:1, 1000:1, 1500:1, 2000:1 or 3000:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the uniform mixing in step (1) is carried out in a polytetrafluoroethylene reactor.

[0017] Preferably, the concentration of the graphene oxide in step (1) is 0.5-12 mg / mL, for example, 0.5 mg / mL, 2 mg / mL, 5 mg / mL, 8 mg / mL or 12 mg / mL, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0018] Preferably, the chemical etchant in step (1) comprises any one of hydrogen peroxide solution, sodium hydroxide solution or potassium hydroxide solution, or a combination of at least two of them. Typical but non-limiting combinations include a combination of hydrogen peroxide solution and sodium hydroxide solution, a combination of sodium hydroxide solution and potassium hydroxide solution, or a combination of hydrogen peroxide solution, sodium hydroxide solution and potassium hydroxide solution.

[0019] The selection of the chemical etchant is conducive to obtaining microporous and mesoporous plasma transmission channels.

[0020] Preferably, the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 28-32wt%, for example, 28wt%, 29wt%, 30wt%, 31wt% or 32wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] Preferably, the concentration of the sodium hydroxide solution and the potassium hydroxide solution is 0.05-0.2 mol / L, for example, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L or 0.2 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the temperature of the hydrothermal treatment in step (1) is 170-190°C, for example, 170°C, 175°C, 180°C, 185°C or 190°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the hydrothermal treatment time in step (1) is 10-14 h, for example, 10 h, 11 h, 12 h, 13 h or 14 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the hydrothermal treatment in step (1) is carried out in a forced air drying oven.

[0025] After in-situ chemical etching of hydrogen peroxide in a hydrothermal process, a graphene hydrogel with a large number of micro / mesoporous structures was obtained, which increased the specific surface area of ​​the material, increased the adsorption sites of ions, promoted the rapid transport of ions, and was beneficial to providing desalination capacity.

[0026] Preferably, the soaking in step (1) is carried out in deionized water.

[0027] Preferably, the soaking time in step (1) is 2-3 days, for example, 2 days, 2.5 days or 3 days, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] The resulting graphene hydrogel was soaked in deionized water to remove excess hydrogen peroxide.

[0029] Preferably, the freeze-drying time in step (1) is 12-72 h, for example, 12 h, 24 h, 36 h, 48 h or 72 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] The graphene foam obtained after freeze drying can not only remove the moisture in the original graphene hydrogel to obtain a dry electrode material, but also retain a large number of micro / mesoporous structures inside the graphene.

[0031] Preferably, the temperature of the annealing treatment in step (1) is 200-1200°C, for example, 200°C, 400°C, 600°C, 800°C or 1200°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] The annealing treatment can effectively improve the conductivity of the graphene electrode material. If the temperature of the annealing treatment is too high, the number of oxygen-containing functional groups will decrease and the wettability will decrease; if the temperature is too low, the degree of reduction will be low and the conductivity will not be improved.

[0033] Preferably, the annealing time in step (1) is 2-6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the annealing treatment in step (1) is performed in a nitrogen atmosphere.

[0035] Preferably, the composite conductive agent in step (2) comprises carbon black and polyvinylidene fluoride.

[0036] Preferably, the mass ratio of the powder obtained after grinding in step (2) to carbon black and polyvinylidene fluoride is (7.5-8.5):1:1, for example, it can be 7.5:1:1, 7.8:1:1, 8:1:1, 8.2:1:1 or 8.5:1:1, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the solid-liquid mass ratio of the total amount of the powder obtained after grinding in step (2) and the composite conductive agent to the organic solvent is 1:(4.5-5.5), for example, it can be 1:4.5, 1:4.8, 1:5, 1:5.2 or 1:5.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] Preferably, the organic solvent in step (2) comprises N-methylpyrrolidone.

[0039] Preferably, the coating treatment in step (2) is performed on carbon cloth.

[0040] Preferably, the drying temperature in step (2) is 50-80°C, for example, 50°C, 60°C, 70°C or 80°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0041] Preferably, the drying time in step (2) is 10-14 h, for example, 10 h, 11 h, 12 h, 13 h or 14 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] Preferably, the time of the plasma treatment in step (2) is 0.5-5 min, for example, 0.5 min, 1 min, 2 min, 3 min, 4 min or 5 min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] The plasma treatment time is within a reasonable range, which can improve the degree of wetting between the electrode surface and the treatment liquid, thereby accelerating ion transmission.

[0044] Preferably, the gas used for the plasma treatment in step (2) includes any one of oxygen, ammonia or air, or a combination of at least two of them. Typical but non-limiting combinations include a combination of oxygen and ammonia, a combination of ammonia and air, or a combination of oxygen, ammonia and air.

[0045] Preferably, the plasma treatment in step (2) is carried out in a plasma cleaning machine.

[0046] The plasma treatment modifies the surface of the electrode with hydrophilic functional groups, thereby improving the hydrophilicity of the electrode and accelerating the rapid transmission and adsorption of ions.

[0047] As a preferred technical solution of the preparation method described in the first aspect of the present invention, the preparation method comprises the following steps:

[0048] (1) uniformly mixing graphene oxide and a chemical etchant in a volume ratio of (100-3000):1, and subjecting the mixture to a hydrothermal treatment at 170-190°C for 10-14h to obtain a graphene hydrogel; the obtained graphene hydrogel is sequentially soaked in deionized water for 2-3d, freeze-dried for 12-72h, and annealed at 200-1200°C in a nitrogen atmosphere for 2-6h to obtain a graphene foam;

[0049] The concentration of the graphene oxide is 0.5-12 mg / mL; the chemical etchant includes any one of hydrogen peroxide solution, sodium hydroxide solution or potassium hydroxide solution or a combination of at least two thereof; the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 28-32 wt %; the concentrations of the sodium hydroxide solution and the potassium hydroxide solution are 0.05-0.2 mol / L;

[0050] (2) grinding the graphene foam obtained in step (1), mixing it with carbon black, polyvinylidene fluoride and an organic solvent, and then coating it on a carbon cloth and drying it at 50-80° C. for 10-14 h to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment in a plasma cleaning machine for 0.5-5 min to obtain the graphene electrode material;

[0051] The mass ratio of the powder obtained after grinding to carbon black and polyvinylidene fluoride is (7.5-8.5):1:1; the solid-liquid mass ratio of the total amount of the powder obtained after grinding, carbon black and polyvinylidene fluoride to the organic solvent is 1:(4.5-5.5).

[0052] In a second aspect, the present invention provides a graphene electrode material, which is prepared by the preparation method described in the first aspect.

[0053] The graphene electrode material provided by the present invention has a multi-level pore structure. The three-dimensional honeycomb structure avoids the close stacking of graphene. The micron-sized macropores can shorten the diffusion distance of salt ions to the inner pores and show an interconnected network structure. The presence of holes greatly reduces the tortuous path and promotes the rapid transfer of ions. After adjusting the reduction degree of the material, the rapid transfer of electrons can be promoted to obtain an electrode material with excellent conductive properties, thereby reducing the energy consumption of the CDI technology desalination process. After O2 - After plasma treatment, the number of hydrophilic oxygen-containing functional groups increases, which can promote the contact between the electrode material and the treatment solution and increase the effective contact area, thereby achieving a higher desalination capacity.

[0054] In a third aspect, the present invention provides an application of the graphene electrode material as described in the second aspect, wherein the graphene electrode material is used for capacitive deionization and desalination and / or removal of heavy metal ions in saline wastewater.

[0055] Preferably, the voltage of the capacitive deionization and desalination is 0.8-1.6V, for example, 0.8V, 1V, 1.2V, 1.4V or 1.6V, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0056] Preferably, the flow rate of the capacitive deionization desalination is 10-25 mL / min, for example, 10 mL / min, 15 mL / min, 20 mL / min or 25 mL / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0057] Preferably, the concentration of the salt solution used for capacitive deionization is 100-2000 mg / L, for example, it can be 100 mg / L, 500 mg / L, 1000 mg / L, 1500 mg / L or 2000 mg / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] Preferably, the salt solution comprises any one of sodium chloride solution, nickel chloride solution, copper chloride solution, cobalt chloride solution, cadmium chloride solution or lead chloride solution, or a combination of at least two of sodium chloride solution, nickel chloride solution, copper chloride solution, cobalt chloride solution, cadmium chloride solution or lead chloride solution. Typical but non-limiting combinations include a combination of sodium chloride solution and nickel chloride solution, a combination of copper chloride solution, cobalt chloride solution, cadmium chloride solution and lead chloride solution, or a combination of sodium chloride solution, nickel chloride solution, copper chloride solution, cobalt chloride solution, cadmium chloride solution and lead chloride solution.

[0059] The process of capacitive deionization and desalination is as follows: graphene electrode materials are placed on both sides of the CDI. After the raw material liquid enters the device, the electrodes on both sides are charged with opposite charges when the power is turned on. At this time, the negatively charged side attracts Na + , Cl - Adsorbed on the positively charged side, forming an electrical double layer. When the electrodes are reversed, the charges on both sides are reversed, forming an electrical double layer of Na + , Cl - Gradually desorb.

[0060] Preferably, the concentration of heavy metal ions in the saline wastewater is 500-1300 mg / L, for example, 500 mg / L, 700 mg / L, 900 mg / L, 1100 mg / L or 1300 mg / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] Preferably, the heavy metal ions in the saline wastewater include any one of copper ions, nickel ions or cobalt ions, or a combination of at least two of them. Typical but non-limiting combinations include a combination of copper ions and nickel ions, a combination of nickel ions and cobalt ions, or a combination of copper ions, nickel ions and cobalt ions.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The preparation method provided by the present invention prepares a graphene porous structure having a large number of micropores and mesopores by chemical etching and hydrothermal method, thereby increasing the specific surface area of ​​the electrode material, and combining with plasma treatment technology to regulate the content of oxygen-containing functional groups on the surface of the graphene electrode material, thereby increasing the hydrophilicity of the electrode material, accelerating the rapid transmission and adsorption of ions, thereby improving the desalination capacity of the CDI technology, and the adsorption capacity can reach 35.66 mg / g; by controlling the annealing temperature of the graphene hydrogel to regulate the reduction degree of the material, the rapid transmission of electrons is promoted, and the electrode material with excellent conductive performance is obtained, thereby reducing the energy consumption of the desalination process of the CDI technology, and the coulomb efficiency can reach 0.84, thereby achieving the goal of high-efficiency capacitive deionization and desalination. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 It is a graph showing the change in adsorption capacity of the graphene electrode materials provided in Examples 1-3 of the present invention and Comparative Example 1;

[0065] Figure 2 This is a graph showing the variation in adsorption capacity of the graphene electrode precursor provided in Comparative Examples 2-5 of the present invention. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] Example 1

[0068] This embodiment provides a graphene electrode material, and a method for preparing the graphene electrode material comprises the following steps:

[0069] (1) uniformly mixing graphene oxide and hydrogen peroxide solution in a volume ratio of 300:1, and hydrothermally treating at 180°C for 12 h to obtain graphene hydrogel; the obtained graphene hydrogel was sequentially soaked in deionized water for 2 d, freeze-dried for 24 h, and annealed at 400°C in a nitrogen atmosphere for 4 h to obtain graphene foam;

[0070] The concentration of the graphene oxide is 2 mg / mL; the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 30 wt%;

[0071] (2) grinding the graphene foam obtained in step (1), mixing it with carbon black, polyvinylidene fluoride and N-methylpyrrolidone, and then coating it on a carbon cloth and drying it at 60° C. for 12 h to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment in an oxygen atmosphere in a plasma cleaning machine for 0.5 min to obtain the graphene electrode material;

[0072] The mass ratio of the powder obtained after grinding to carbon black and polyvinylidene fluoride is 8:1:1; the solid-liquid mass ratio of the total amount of the powder obtained after grinding, carbon black and polyvinylidene fluoride to N-methylpyrrolidone is 1:5.

[0073] The obtained graphene electrode material is used for capacitive deionization and desalination. The voltage of the capacitive deionization and desalination is 1.2V, the flow rate is 15mL / min, and the concentration of the sodium chloride solution used is 500mg / L. The adsorption capacity change diagram of the graphene electrode material is as follows: Figure 1 As shown, the adsorption capacity of graphene electrode materials can reach 35.66 mg / g, and the coulombic efficiency can reach 0.66.

[0074] The obtained graphene electrode material is used for removing heavy metal ions in saline wastewater. The concentration of copper ions in the saline wastewater is 1000 mg / L, and the adsorption amount of copper ions by the graphene electrode material is 89.96 mg / g, indicating that the hydrophilic graphene electrode material also has good heavy metal adsorption capacity.

[0075] Example 2

[0076] This embodiment provides a graphene electrode material, and a method for preparing the graphene electrode material comprises the following steps:

[0077] (1) Graphene oxide and hydrogen peroxide solution in a volume ratio of 100:1 were uniformly mixed, and the mixture was hydrothermally treated at 190° C. for 10 h to obtain a graphene hydrogel; the obtained graphene hydrogel was sequentially soaked in deionized water for 2 d, freeze-dried for 12 h, and annealed at 200° C. for 6 h in a nitrogen atmosphere to obtain a graphene foam;

[0078] The concentration of the graphene oxide is 0.5 mg / mL; the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 28 wt%;

[0079] (2) grinding the graphene foam obtained in step (1), mixing it with carbon black, polyvinylidene fluoride and N-methylpyrrolidone, and then coating it on a carbon cloth and drying it at 50° C. for 14 h to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment in an ammonia atmosphere in a plasma cleaning machine for 0.5 min to obtain the graphene electrode material;

[0080] The mass ratio of the powder obtained after grinding to carbon black and polyvinylidene fluoride is 7.5:1:1; the solid-liquid mass ratio of the total amount of the powder obtained after grinding, carbon black and polyvinylidene fluoride to N-methylpyrrolidone is 1:4.5.

[0081] The obtained graphene electrode material is used for capacitive deionization and desalination. The voltage of the capacitive deionization and desalination is 0.8V, the flow rate is 10mL / min, and the concentration of the sodium chloride solution used is 100mg / L. The adsorption capacity change diagram of the graphene electrode material is as follows: Figure 1 As shown, the adsorption capacity of graphene electrode material can reach 34.93 mg / g, and the coulombic efficiency can reach 0.70.

[0082] Example 3

[0083] This embodiment provides a graphene electrode material, and a method for preparing the graphene electrode material comprises the following steps:

[0084] (1) uniformly mixing graphene oxide and hydrogen peroxide solution in a volume ratio of 3000:1, and hydrothermally treating at 170°C for 14 h to obtain graphene hydrogel; the obtained graphene hydrogel was sequentially soaked in deionized water for 3 d, freeze-dried for 72 h, and annealed at 600°C for 2 h in a nitrogen atmosphere to obtain graphene foam;

[0085] The concentration of the graphene oxide is 12 mg / mL; the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 32 wt%;

[0086] (2) grinding the graphene foam obtained in step (1), mixing it with carbon black, polyvinylidene fluoride and N-methylpyrrolidone, and then coating it on a carbon cloth and drying it at 80° C. for 10 h to obtain a graphene electrode precursor; subjecting the obtained graphene electrode precursor to plasma treatment in an air atmosphere in a plasma cleaning machine for 0.5 min to obtain the graphene electrode material;

[0087] The mass ratio of the powder obtained after grinding to carbon black and polyvinylidene fluoride is 8.5:1:1; the solid-liquid mass ratio of the total amount of the powder obtained after grinding, carbon black and polyvinylidene fluoride to N-methylpyrrolidone is 1:5.5.

[0088] The obtained graphene electrode precursor and graphene electrode material are used for capacitive deionization and desalination. The voltage of the capacitive deionization and desalination is 1.6V, the flow rate is 25mL / min, and the concentration of the sodium chloride solution used is 2000mg / L. The adsorption capacity change diagram of the graphene electrode material is as shown in Figure 1 As shown, the adsorption capacity of graphene electrode materials can reach 33.06 mg / g, and the Coulomb efficiency can reach 0.69.

[0089] Example 4

[0090] This embodiment provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Embodiment 1 is that, except for adjusting the time of the plasma treatment in step (2) to 5 minutes, the rest is the same as that of Embodiment 1.

[0091] The adsorption capacity of the obtained graphene electrode material can reach 35.60 mg / g, and the coulombic efficiency can reach 0.65, indicating that the plasma treatment time is long and will not lead to a significant improvement in surface wettability. At this time, the desalination capacity has no obvious change compared with Example 1.

[0092] Example 5

[0093] This embodiment provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Embodiment 1 is that, except that the temperature of the annealing treatment in step (1) is adjusted to 1200° C., the rest is the same as that of Embodiment 1.

[0094] The adsorption capacity of the obtained graphene electrode material can reach 30.25 mg / g, and the coulombic efficiency can reach 0.84. A high annealing temperature can improve the conductivity of the electrode material, but a higher annealing temperature will affect the hydrophilicity of the electrode material and thus limit its adsorption capacity.

[0095] Example 6

[0096] This embodiment provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that the hydrogen peroxide solution in step (1) is replaced by an equal volume of a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.05 mol / L. The rest is the same as that of Example 1.

[0097] The adsorption capacity of the obtained graphene electrode material can reach 25.76 mg / g, and the coulombic efficiency can reach 0.75; using sodium hydroxide solution as a chemical etchant, the graphene wall has a porous structure, with a large number of micropores and small mesopores on the plane, resulting in a larger specific surface area, which is conducive to the good transmission of ions and reduces the ion diffusion resistance, thereby improving the desalination capacity.

[0098] Example 7

[0099] This embodiment provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that the copper ions in the saline wastewater are replaced with cobalt ions at an equal concentration, and the rest is the same as that of Example 1.

[0100] The adsorption capacity of cobalt ions by the obtained graphene electrode material is 78.99 mg / g, indicating that the hydrophilic graphene electrode material has good heavy metal adsorption capacity.

[0101] Example 8

[0102] This embodiment provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that the copper ions in the saline wastewater are replaced with nickel ions at an equal concentration, and the rest is the same as that of Example 1.

[0103] The adsorption capacity of nickel ions by the graphene electrode material is 91.80 mg / g, indicating that the hydrophilic graphene electrode material has good heavy metal adsorption capacity.

[0104] Comparative Example 1

[0105] This comparative example provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that step (1) does not include an annealing step, and the rest is the same as that of Example 1.

[0106] The adsorption capacity variation of the graphene electrode material is shown in FIG. Figure 1 As shown, the adsorption capacity of the graphene electrode material is 27.09 mg / g, and the coulombic efficiency is 0.68, indicating that the effective contact area between the unannealed graphene electrode material and the solution is increased after hydrophilic treatment, which promotes the effective adsorption of salt ions and thus improves the desalination capacity.

[0107] Comparative Example 2

[0108] This comparative example provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that step (2) does not include a plasma treatment step, and the rest is the same as that of Example 1.

[0109] The adsorption capacity change of the obtained graphene electrode precursor is shown in the figure Figure 2 As shown, the adsorption capacity of the graphene electrode precursor is 27.52 mg / g, and the coulombic efficiency is 0.81, indicating that the degree of wettability of the surface of the graphene electrode precursor without plasma treatment with the treatment liquid is reduced, which reduces the ion transmission and the desalination performance.

[0110] Comparative Example 3

[0111] This comparative example provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 2 is that step (2) does not include a plasma treatment step, and the rest is the same as that of Example 2.

[0112] The adsorption capacity change of the obtained graphene electrode precursor is shown in the figure Figure 2 As shown, the adsorption capacity of the graphene electrode precursor is 32.14 mg / g and the coulombic efficiency is 0.70, indicating that the desalination performance of the graphene electrode precursor without plasma treatment is reduced.

[0113] Comparative Example 4

[0114] This comparative example provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 3 is that step (2) does not include a plasma treatment step, and the rest is the same as that of Example 3.

[0115] The adsorption capacity change of the obtained graphene electrode precursor is shown in the figure Figure 2 As shown, the adsorption capacity of the graphene electrode precursor can reach 23.84 mg / g, and the coulombic efficiency is 0.83, indicating that the desalination performance of the graphene electrode precursor without plasma treatment is reduced.

[0116] Comparative Example 5

[0117] This comparative example provides a graphene electrode material. The difference between the preparation method of the graphene electrode material and that of Example 1 is that step (1) does not include an annealing step, and step (2) does not include a plasma treatment step. The rest is the same as that of Example 1.

[0118] The adsorption capacity change of the obtained graphene electrode precursor is shown in the figure Figure 2 As shown, the adsorption capacity of the graphene electrode precursor is 18.95 mg / g and the coulombic efficiency is 0.58, indicating that the desalination performance of the graphene electrode precursor without annealing and plasma treatment is significantly reduced.

[0119] In summary, the preparation method provided by the present invention prepares a graphene porous structure having a large number of micropores and mesopores by chemical etching and hydrothermal method, thereby increasing the specific surface area of ​​the electrode material, and combining plasma treatment technology to regulate the content of oxygen-containing functional groups on the surface of the graphene electrode material, thereby increasing the hydrophilicity of the electrode material, accelerating the rapid transmission and adsorption of ions, thereby improving the desalination capacity of the CDI technology, and the adsorption capacity can reach 35.66 mg / g; by controlling the annealing temperature of the graphene hydrogel to regulate the degree of reduction of the material, the rapid transmission of electrons is promoted, and an electrode material with excellent conductive properties is obtained, thereby reducing the energy consumption of the desalination process of the CDI technology, and the coulomb efficiency can reach 0.84, achieving the goal of high-efficiency capacitive deionization and desalination.

[0120] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a graphene electrode material for capacitive deionization and / or removal of heavy metal ions in saline wastewater, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing graphene oxide and a chemical etchant, and subjecting the mixture to a hydrothermal treatment to obtain a graphene hydrogel; and sequentially subjecting the obtained graphene hydrogel to a soaking, freeze-drying, and annealing treatment to obtain a graphene foam; (2) The graphene foam obtained in step (1) is ground and mixed with a composite conductive agent and an organic solvent, and then coated and dried to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment to obtain the graphene electrode material; The temperature of the annealing treatment in step (1) is 200-400°C; The gas used for the plasma treatment in step (2) includes any one of oxygen, ammonia or air, or a combination of at least two of them.

2. The preparation method according to claim 1, characterized in that: The volume ratio of the graphene oxide to the chemical etchant in step (1) is (100-3000):

1.

3. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide in step (1) is 0.5-12 mg / mL.

4. The preparation method according to claim 1, characterized in that: The chemical etchant in step (1) includes any one of hydrogen peroxide solution, sodium hydroxide solution or potassium hydroxide solution, or a combination of at least two of them.

5. The preparation method according to claim 4, characterized in that: The mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 28-32wt%.

6. The preparation method according to claim 4, characterized in that: The concentrations of the sodium hydroxide solution and the potassium hydroxide solution are 0.05-0.2 mol / L.

7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal treatment in step (1) is 170-190°C.

8. The preparation method according to claim 1, characterized in that: The time of the hydrothermal treatment in step (1) is 10-14 hours.

9. The preparation method according to claim 1, characterized in that: The immersion in step (1) is carried out in deionized water.

10. The preparation method according to claim 1, characterized in that: The soaking time in step (1) is 2-3 days.

11. The preparation method according to claim 1, characterized in that: The freeze-drying time in step (1) is 12-72 hours.

12. The preparation method according to claim 1, characterized in that: The annealing time in step (1) is 2-6 hours.

13. The preparation method according to claim 1, characterized in that: The annealing treatment in step (1) is performed in a nitrogen atmosphere.

14. The preparation method according to claim 1, characterized in that: The composite conductive agent in step (2) includes carbon black and polyvinylidene fluoride.

15. The preparation method according to claim 14, characterized in that: The mass ratio of the powder obtained after grinding in step (2) to carbon black and polyvinylidene fluoride is (7.5-8.5):1:

1.

16. The preparation method according to claim 1, characterized in that: The solid-liquid mass ratio of the total amount of the powder obtained after grinding and the composite conductive agent to the organic solvent in step (2) is 1:(4.5-5.5).

17. The preparation method according to claim 1, characterized in that: The organic solvent in step (2) includes N-methylpyrrolidone.

18. The preparation method according to claim 1, characterized in that: The coating process in step (2) is performed on the carbon cloth.

19. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 50-80°C.

20. The preparation method according to claim 1, characterized in that: The drying time in step (2) is 10-14 hours.

21. The preparation method according to claim 1, characterized in that: The time of the plasma treatment in step (2) is 0.5-5 min.

22. The preparation method according to claim 1, characterized in that: The plasma treatment in step (2) is carried out in a plasma cleaning machine.

23. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing graphene oxide and a chemical etchant in a volume ratio of (100-3000):1, and subjecting the mixture to a hydrothermal treatment at 170-190°C for 10-14h to obtain a graphene hydrogel; the obtained graphene hydrogel is sequentially soaked in deionized water for 2-3d, freeze-dried for 12-72h, and annealed at 200-400°C in a nitrogen atmosphere for 2-6h to obtain a graphene foam; The concentration of the graphene oxide is 0.5-12 mg / mL; the chemical etchant includes any one of hydrogen peroxide solution, sodium hydroxide solution or potassium hydroxide solution or a combination of at least two thereof; the mass fraction of hydrogen peroxide in the hydrogen peroxide solution is 28-32 wt %; the concentrations of the sodium hydroxide solution and the potassium hydroxide solution are 0.05-0.2 mol / L; (2) The graphene foam obtained in step (1) is ground and mixed with carbon black, polyvinylidene fluoride and an organic solvent, and then coated on a carbon cloth and dried at 50-80° C. for 10-14 hours to obtain a graphene electrode precursor; the obtained graphene electrode precursor is subjected to plasma treatment in a plasma cleaning machine for 0.5-5 minutes to obtain the graphene electrode material; The mass ratio of the powder obtained after grinding to carbon black and polyvinylidene fluoride is (7.5-8.5):1:1; the solid-liquid mass ratio of the total amount of the powder obtained after grinding, carbon black and polyvinylidene fluoride to the organic solvent is 1:(4.5-5.5).

24. A graphene electrode material, characterized in that: The graphene electrode material is prepared by the preparation method described in any one of claims 1-23.

25. A use of the graphene electrode material as claimed in claim 24, characterized in that: The graphene electrode material is used for capacitive deionization and desalination and / or removal of heavy metal ions in saline wastewater.

26. The use according to claim 25, characterized in that The voltage of the capacitor deionization and desalination is 0.8-1.6V.

27. The use according to claim 25, characterized in that The flow rate of the capacitive deionization desalination is 10-25 mL / min.

28. The use according to claim 25, characterized in that The concentration of the salt solution used in the capacitive deionization desalination is 100-2000 mg / L.

29. The use according to claim 28, characterized in that The salt solution includes any one of sodium chloride solution, nickel chloride solution, copper chloride solution, cobalt chloride solution, cadmium chloride solution or lead chloride solution, or a combination of at least two of them.

30. The use according to claim 25, characterized in that The concentration of heavy metal ions in the saline wastewater is 500-1300 mg / L.

31. The use according to claim 25, characterized in that The heavy metal ions in the saline wastewater include any one of copper ions, nickel ions or cobalt ions, or a combination of at least two of them.

Citation Information

Patent Citations

  • Preparation method of nanometer compounding capacitor type desalting electrode of carbon nanometer pipe / graphene sandwich structure

    CN102583654A

  • Composite film comprising graphene oxide coating layer, porous polymer support comprising same, and method for preparing same

    CN106102884A

  • Preparation method of hierarchical porous three-dimensional structure graphene electrocatalyst

    CN111250073A

  • Preparation method of nitrogen-doped three-dimensional porous graphene hydrogel electrode material, electrode and application thereof

    CN113479872A